Unicornuate Uterus with a Non-Communicating Rudimentary Horn in a Palestinian Patient with Familial Mediterranean Fever: Case Report - Darras, Osama; Abu Osba, Amal; Massarweh, Khalid (AL-Kindy College Medical Journal, 2023)
Rudimentary non-communicating functional uterine horn with unicornuate uterus, originating from anomalous embryological development of one Mullerian duct, is prone to different complications either at the gynecological or obstetrical level such as chronic pelvic pain, hematometra, subfertility and decreased quality of life. This unique case report presents a 14-year-old female with a history of severe chronic pelvic pain. She was diagnosed with Familial Mediterranean Fever (FMF) and had an appendectomy for suspected appendicitis within the symptoms’ interval. Ultrasound showed a right 5*6 cm right complex cystic mass assuming ovarian in place. She underwent a suspected endometrioma cystectomy operation and was diagnosed with left unicornuate uterus with right functional non-communicating rudimentary horn. The patient was followed up and mentioned marked improvement of her previous pain attacks. Her family members observed marked improvement in her usual daily activities and quality of life. Occult non-communicating uterine horn are frequently misdiagnosed due to its rarity and unspecific symptoms. The diagnosis of Mullerian anomalies should be added to the differential diagnoses for women with infertility, chronic abdominal and pelvic pain, and dysmenorrhea to avoid the patients’ agony and to alleviate their quality of life.